Study of Economic Inequality in The Agglomeration Region of Malang Raya - Subagyo, Widiyanto Hari; Hamidah Imadudin, Annisa; Nurul H, Agustina (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
Each region has the potential to grow and develop according to their respective conditions. The difference in these conditions results in inequality in the speed of growth and development in each region, this condition is known as disparity. The gap will be a problem if there is a gap that is too large and is caused by the wrong development system, so that it can be a cause of unrest, dissatisfaction and even a separatist movement that wants to separate itself from the Unitary State of the Republic of Indonesia. The basic problem in regional development in the Metropolitan Area, especially Malang Raya is the gap between regions where development is monocentric, centered on Malang City. Responding to such conditions, it is necessary to formulate a regional disparity system in Malang Raya, to find out the extent to which development and regional growth are concentrated in Malang Raya. In addition, it is hoped that through the formulation of the regional disparity system, it can be a reference so that the direction can minimize regional disparities in Malang Raya.